2011
DOI: 10.1021/jf104217g
|View full text |Cite
|
Sign up to set email alerts
|

Use of Saccharomyces cerevisiae and Caenorhabditis elegans as Model Organisms To Study the Effect of Cocoa Polyphenols in the Resistance to Oxidative Stress

Abstract: Developing functional foods to improve the quality of life for elderly people has great economic and social impact. Searching for and validating ingredients with in vivo antioxidant effects is one of the key steps in developing this kind of food. Here we describe the combined use of simple biological models and transcriptomics to define the functional intracellular molecular targets of a polyphenol-enriched cocoa powder. Cocoa powder supplemented culture medium led to increased resistance to oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 38 publications
8
74
0
3
Order By: Relevance
“…Blueberry extract promotes longevity in C. elegans and Drosophila (Peng et al 2012;Wilson et al 2006). Cocoa contains abundant flavonoids and promotes longevity and resistance to oxidative stress in worms (Martorell et al 2011). Nectarine and açai extracts promote the survival in Drosophila under oxidative stress and fed high-fat diets (Boyd et al 2011;Sun et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Blueberry extract promotes longevity in C. elegans and Drosophila (Peng et al 2012;Wilson et al 2006). Cocoa contains abundant flavonoids and promotes longevity and resistance to oxidative stress in worms (Martorell et al 2011). Nectarine and açai extracts promote the survival in Drosophila under oxidative stress and fed high-fat diets (Boyd et al 2011;Sun et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The biofortified oranges exerted a higher protective effect than control oranges despite its slightly lower content of xanthophylls (oxygenated carotenoids also described as dietary antioxidants (Haegele et al, 2000)), which supports the strong antioxidant effect of dietary β-carotene reported in previous studies (Jialal et al, 1991;Meydani et al, 1994;Nakagawa et al, 1996). The effect of dietary β-carotene against oxidative stress achieved in this work (70% worm survival after hydrogen peroxide treatment) is similar to the effect reported for cocoa polyphenols (Martorell et al, 2011) and Tonalin (a conjugated linoleic acid commercial mixture) (Martorell et al, 2012). The mechanism of the antioxidant activity of β-carotene is related to this compound's hydrophobic character and ability to quench singlet oxygen and deactivate free radicals (Burton and Ingold, 1984;Rice-Evans et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…Establishment of a C. elegans system to evaluate the in vivo antioxidant effect of orange juice C. elegans has been widely used as a model to study the in vivo antioxidant capacity of different pure compounds and certain plant extracts (Artal-Sanz et al, 2006;Martorell et al, 2011;Martorell et al, 2012;Van Raamsdonk and Hekimi, 2010) but not the juice from fruits or vegetables. Therefore, it was necessary to optimize certain essential aspects concerning the experimental method prior to performing the bioassays with the orange fruit.…”
Section: Silencing Of Csβ-chx Results In Increased β-Carotene In the mentioning
confidence: 99%
“…elegans; these effects were fully dependent on the polyphenols present in the cocoa powder and on SIR-2.1, a worm sirtuin (Martorell et al, 2011).…”
Section: Beyond Resveratrol: Flavonoids and Other Phenolic Compoundsmentioning
confidence: 99%